Analisis Pengaruh Kualitas Produk dan Inovasi Produk terhadap Keunggulan Kompetitif pada Hokben Daerah Istimewa Yogyakarta - Binarwati, Ajeng; Yamit, Zulian (Jurnal Indonesia Sosial Sains, 2022)
The purpose of this study is to identify Product Quality influence on Competitive Advantage HokBen Yogyakarta, To identify Product Innovation affects Competitive Advantage HokBen Yogyakarta, To identify I Novasi Product and Product Quality influence simultaneously on HokBen Competitive Advantage Yogyakarta. The sample taken was some of HokBen's consumers in Yogyakarta who numbered 100. The method used in data testing and analysis is SPSS 24. The results of this study show that Product Quality has a significant effect on Competitive Advantage, Product Innovation has a significant effect on Competitive Advantage, Product Quality and Product Innovation have a simultaneous effect on Competitive Advantage.